2016
DOI: 10.3892/ijo.2016.3630
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia upregulates Malat1 expression through a CaMKK/AMPK/HIF-1α axis

Abstract: Increased expression levels of the long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (Malat1) have been associated with enhanced proliferation and metastasis of several cancer cell types. Hypoxia, a hallmark characteristic of solid tumors, has been linked to an increase in the activity of the ATP-generating AMPK protein. Since Malat1 was recently shown to be upregulated during hypoxia, the objective of this study was to determine the contribution of AMPK in the mechanistic pathways reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 41 publications
0
61
1
Order By: Relevance
“…More importantly, previous studies reported that hypoxia provides an important driving factor in the expression pattern of various lncRNAs including MALAT1. For example, Sallé‐Lefort et al demonstrated lncRNA‐MALAT1 expression is regulated in hypoxic conditions by a CaMKK/AMPK/HIF‐1α axis . In another study, Brock et al found that the levels of lncRNA‐MALAT1 were significantly increased in hypoxic human pulmonary artery smooth muscle .…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, previous studies reported that hypoxia provides an important driving factor in the expression pattern of various lncRNAs including MALAT1. For example, Sallé‐Lefort et al demonstrated lncRNA‐MALAT1 expression is regulated in hypoxic conditions by a CaMKK/AMPK/HIF‐1α axis . In another study, Brock et al found that the levels of lncRNA‐MALAT1 were significantly increased in hypoxic human pulmonary artery smooth muscle .…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to have a role particularly in response to hormones and stresses that acutely control intracellular calcium, including processes such as the regulation of food intake by hypothalamic neurons in mice 70,71 , activation of antigen and thrombin receptors in immune and endothelial cells, respectively 72,73 , and stimulation of mitochondrial activity by thyroid hormone 74,75 . Notably, CAMKK2 has also been shown to activate AMPK following cellular stresses, including amino acid starvation 76 , hypoxia 77,78 and cell detachment from the matrix 79 . In LKB1-null cells, CAMKK2 is able to maintain some AMPK activity that is still sensitive to changes in the ATP-to-AMP ratio 80 .…”
Section: Ampk Structure and Activationmentioning
confidence: 99%
“…AMPK is a critical energy sensor that discerns the balance between ATP and AMP in the cytosol; SIRT1 is a redox‐sensing nicotinamide adenine dinucleotide‐dependent enzyme that deacetylates target proteins that play important roles in the regulation of cellular processes involved in metabolism and homeostasis; and HIF‐1α activates the transcription of genes that promote oxygen delivery and reduce oxygen utilization, switching cells from oxidative to glycolytic metabolism . These three molecules interact with, reinforce and regulate each other and share common targets . Additionally, SIRT1 appears to induce HIF‐2α, which may also promote autophagic clearance of damaged organelles .…”
Section: Novel Mechanisms By Which Sglt2 Inhibitors May Promote Cardimentioning
confidence: 99%